HOZIRGI KUNDA INGLIZ TILINI O’RGANISHDA YOSHLAR YUZLASHADIGAN QIYINCHILIKLAR - Hasanova Zuhra Abdimurod qizi SamDCHTI 2-bosqich talabasi Ilmiy raxbar: Sh.O.Mamayoqubova (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2023)
In today’s era of development and progress, special attention is paid to each area. A whole society, the earth faces the need to exchange information with each other for further development. To meet this need, nations must understand each other. The need for understanding requires learning foreign languages. Based on this, we can easily say that there is a great need and interest in learning foreign languages. For this reason, every country allocates large investments and projects to facilitate the learning of foreign languages ​​for young people and people of any age who are eager to learn foreign languages. In particular, there is a strong effort to learn and teach English, which is the most common and widely used language today. Because English is the language of the Internet. English is the language of science, technology, tourism and diplomatic relations. For this reason, the need to learn English is very important. However, students face several difficulties. This article talks about the difficulties and problems encountered in the process of learning English.‌‌